ANALISIS RISIKO USAHATANI KOPI SPECIALTY JAVA PREANGER - Sari, Nur; Pardian, Pandi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2018)
Maju Mekar as a farmers group has productivity. it was only reach 0,01 ton/ha, which indicate risks. The objectives of this research were to identify the causes of risk and how much the risk of coffee farming affect Maju Mekar farmer group. The research used descriptive qualitative and case study research method. Risk causes identification in Maju Mekar farmer group used fish bone diagram by detailing what causes the failure. Risk analysis using FMEA (Failure Mode and Effect Analysis) method to obtain a risk based on the highest value of the RPN (Risk Priority Number) and RSV (Risk Score Value) which has to betaken care of immediately. The research result was 12 priority handling risk of coffee farming in Maju Mekar farmer group. Maju Mekar farmer group has been preveting 4 priority risk sources. An alternative strategy that can be done for the 6 priority risks are to by recording the production and cash flow, raw materials (cherries) received, using a pre order payment system for a limited source of capital risk, cultivation of horticultural crops for lack of persistence of farmers, fertilizers not in accordance with SOP, cooperating with other farmer groups to increase production, cultivation of coffee crops according to SOP for less altitude.